Implementation of Android-Based Futsal Court Booking Application Using Flutter (Case Study: Futsal Hayani Kopti, West Cengkareng) - Veri Arinal; Mesra Betty Yel; I Komang Dewa Ananda Putra; Fauzan Azima; Mohammad Farhan; Muhammad Ikhsan Hakim; Dadang Mulyana Iskandar; Sutisna Sutisna (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid development of information technology has encouraged service providers to improve efficiency and service quality, including in futsal court rental services. At Futsal Hayani Kopti Cengkareng Barat, the court booking process is still conducted manually through phone calls or direct visits, which often results in scheduling conflicts, limited access to information, and unstructured data management. These conditions reduce the effectiveness and efficiency of the booking process. This practical work aims to design and implement an Android-based futsal court booking application using the Flutter framework. The developed application provides real-time information on court availability, rental prices, facilities, and online booking features. In addition, the system assists administrators in managing booking schedules and transaction data in a centralized manner. The research method applied is qualitative, employing observation, interviews, documentation, and literature study. System development follows the System Development Life Cycle (SDLC) approach with an internet-based client–server architecture. The implementation results indicate that the application improves booking efficiency, reduces scheduling conflicts, and enhances service quality as well as user satisfaction.